Sistem Monitoring PH dan TDS Air Bekas Tambang Pada Settling Pond Blok III PT. AGM Berbasis Internet Of Things (IOT) - Tamaji, Tamaji; Rabbani, Ahmad; Bhuwana, Mahesa Sangga; Dhaniswara, Erwin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to design and implement an Internet of Things (IoT)-based monitoring system for measuring pH and Total Dissolved Solids (TDS) in post-mining wastewater at the settling pond of Block III, PT. Antang Gunung Meratus (PT. AGM). The system utilizes pH E-201C and Gravity TDS sensors to periodically measure water quality parameters, with data processed by an ESP32 microcontroller and transmitted via Wi-Fi to a cloud platform for real-time monitoring. The data are visualized through a web-based dashboard, while an alert system using LED indicators, buzzer, and Telegram notifications is activated when parameters exceed predefined thresholds. The system architecture integrates sensors, a control unit, communication modules, and actuators such as relays and pumps to enable automated monitoring and response. Testing results indicate that the system achieves reliable accuracy, with pH measurement deviations of approximately ±0.2 and TDS deviations around ±75 ppm compared to manual instruments, corresponding to an error rate below 5%. These results fall within acceptable tolerance limits for water quality monitoring. Overall, the developed system demonstrates effective real-time monitoring capability, reduces manual measurement efforts, and supports early detection of water quality changes. The system also shows potential for further development through integration with automated treatment control and additional environmental parameters, contributing to more efficient and sustainable mining wastewater management.